2017
DOI: 10.5195/jmla.2017.329
|View full text |Cite
|
Sign up to set email alerts
|

Facing reality: the growth of virtual reality and health sciences libraries

Abstract: Virtual reality (VR) is an increasingly hot tech topic. Because VR may be the ultimate virtual project as defined by this column, replacing the real world with a simulated one, it is worthwhile to pause and reflect on its potential and practicality for health sciences libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 3 publications
(3 reference statements)
0
27
0
1
Order By: Relevance
“…Libraries today enhance the learning performance of customers by incorporating virtual reality technology to encourage library patronage [32], learning and playing. Virtual (augmented and mixed) reality is an experience for which a physical user is made to enter a three dimensional virtual world using a headset, computer-powered imaging or mobile device [33]. Several virtual reality devices are now available in academic libraries, e.g.…”
Section: Virtual Reality (Vr)mentioning
confidence: 99%
“…Libraries today enhance the learning performance of customers by incorporating virtual reality technology to encourage library patronage [32], learning and playing. Virtual (augmented and mixed) reality is an experience for which a physical user is made to enter a three dimensional virtual world using a headset, computer-powered imaging or mobile device [33]. Several virtual reality devices are now available in academic libraries, e.g.…”
Section: Virtual Reality (Vr)mentioning
confidence: 99%
“…VR immerses the user in a digitally created environment, mostly via a head‐mounted display (HMD) 2 . There are numerous areas that VR can be applied to, specifically in an educational context, for example, a virtual classroom, where students can interact with a lecturer, 3 and the training of pilots 4 or surgeons 5 . VR is also being used to assist learners with intellectual disabilities, 6 and as a medium for innovative teaching methods, mainly due to the low costs involved, the immersive experience and it is safe to use 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Students prefer to engage in traditional lectures over online courses because they lack self-discipline and they can become too easily distracted during online learning (Crook & Schofield, 2017). Applying immersive VR to education may engage students better than MOOCs, removing distractions outside of the learning environment, mimicking the experience of traditional learning experiences (Lessick & Kraft, 2017;Pirker et al, 2018). Existing examples of educational applications of VR have focused on non immersive desktop-VR and have shown that simulating learning environments is highly effective.…”
Section: Introductionmentioning
confidence: 99%